DETERMINANTS OF BLOOD SUGAR REGULATION IN PATIENTS WITH TYPE 1 DIABETES: A SYSTEMATIC LONGITUDINAL ANALYSIS. - Dr Mustafa Ali Hamid; Dr Karan Kumar Maheshwari; Dr Hina; Dr Priya; Dr Manoj Kumar; Dr Marryam Choudhary (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Aim/Objective: To assess glycemic control and discover characteristics that predict glycemic outcomes among people with type 1 diabetes.Methodology:This study observed 130 adults with type 1 diabetes, assessing their glycemic control monthly over three months. Data on sociodemographic, clinical, and behavioral factors were collected using structured questionnaires and clinical records. Laboratory tests followed standardized protocols. Statistical analyses identified predictors of suboptimal glycemic control using SPSS software. Ethical approval and informed consent were obtained.Results:The study included 130 participants, predominantly male (60%) and aged 41-60 years. Most had primary education (54.6%) and were engaged in farming (34.2%). About 76.1% never smoked, and 63.6% had a healthy weight. Non-adherence to treatment was reported by 59.1% of participants. The most prevalent comorbidity was hypertension. (39.1%). Poor glycemic control was detected in 72.7% of participants, with a mean HbA1c of 8.2 ± 1.5%.Conclusion:This study highlights the widespread issue of diabetics having poor glycemic control, emphasizing the need for targeted interventions. Lifestyle factors like overweight/obesity play a crucial role, alongside challenges related to renal function. Moving forward, personalized approaches focusing on adherence and weight management are imperative for improving diabetes care and reducing complications. Keywords: , , , Predictors, .